IMPLEMENTASI KEBIJAKAN PELESTARIAN SENI TRADISIONAL (Studi Kasus di Dinas Kebudayaan dan Pariwisata Kota Bandung) - Dian Susanti (FISIP Universitas Langlangbuana, 2019)
The background of the problem of this research is that the implementation of traditional art preservation policies in the Bandung City Culture and Tourism Office is not yet optimal. From the background of the problem the researcher identifies the problem as follows: How to implement traditional art preservation policies in the Bandung City Culture and Tourism Office. What are the factors supporters and inhibitors of the implementation of traditional art preservation policies in the Bandung City Culture and Tourism Office and what efforts have been made by the Bandung City Culture and Tourism Office in implementing policies on preserving traditional arts in the City of Bandung. The foundation of this theory uses the Policy Implementation theory, the researchers formulated the proposition as follows: